Generating professional development by supporting reflexivity in continuing education: a case study in kindergarten - Talérien, Stéphane Jean; Chaliès, Sébastien; Bertone, Stefano (Swiss Journal of Educational Research, 2021)
This case study proposes, based on an anthropocultural research program, a research-based training scheme that creates the formal conditions for the effective transmission of the rules of ordinary pedagogical practice between two experienced teachers working in the same nursery school. In order to produce their professional development, the two teachers (one in the role of “peer trainer” and the other in the role of “trained peer”) underwent three training episodes : (i) prior access by the peer trainer to a clearer vision of the rules governing his practice to be transmitted (ii) ostensive teaching of these rules by the peer trainer to the trained peer and (iii) two implementations by the trained peer followed each time by an accompanying activity in the form of supervision of the peer trainer. The results obtained show (a) the learning of a new rule by the trained peer enabling him/her to solve a professional difficulty as well as (b) the professional development of the peer trainer following his/her accompaniment of the practice of the trained peer.